1994
DOI: 10.1111/j.1432-1033.1994.tb20091.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymically Produced Cyclic α‐1,3‐Linked and α‐1,6‐Linked Oligosaccharides of d‐Glucose

Abstract: A new type of bacterial enzyme hydrolyzed alternan (Leuconostoc mesenteroides NRRL B-1355 fraction S dextran, an alternating a-l,3-a-1,6-D-glucan) to give rise to a series of oligosaccharides. The oligosaccharide formed in the greatest proportion was a cyclic tetrasaccharide of D-glucosyl residues linked in an alternating a-1,3-a-1,6 fashion. Other saccharide products included isomaltose and a-D-glucopyranosyl-1,3-a-D-g~UCOp~~~~OS~~-~,6-~-glucose. Oligosaccharides of higher degrees of polymerization were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…16) Furthermore, it was found that there is CTS in the reaction mixture containing purified enzyme and alternan. 12) This is the first report relating to the enzymatic synthesis of CTS. Later they examined the substrate specificity of alternanase and reported that CTS was also produced from panose by the enzyme.…”
Section: )mentioning
confidence: 96%
See 1 more Smart Citation
“…16) Furthermore, it was found that there is CTS in the reaction mixture containing purified enzyme and alternan. 12) This is the first report relating to the enzymatic synthesis of CTS. Later they examined the substrate specificity of alternanase and reported that CTS was also produced from panose by the enzyme.…”
Section: )mentioning
confidence: 96%
“…Cyclic tetrasaccharide (CTS; cyclo{ 6) D Glup (1 3) D Glucp (1 6) D Glucp (1 3) D Glup (1 }) is also one of the nonreducing glucooligosaccharides. 12) A system of synthesizing this cyclic oligosaccharide from starch was recently found in Bacillus globisporus C11. A CTS synthesizing mechanism controlled by two enzymes and the sequence of the genes encoding them were reported in succession.…”
mentioning
confidence: 99%
“…4,5) CTS is smaller than the other cyclic glucans mentioned above and has heterogeneous linkages in its structure. Crystal structure analysis showed that CTS is shaped like a plate with a depression on one side, but does not possess a cavity space like cyclodextrins do.…”
Section: Cloning and Sequencing Of The Genes Encoding Cyclicmentioning
confidence: 97%
“…In the present study, we employed a new class of cyclic tetrasaccharide (Scheme ), cyclo ‐{→6)‐α‐ d ‐Glc p ‐(1→3)‐α‐ d ‐Glc p ‐(1→6)‐α‐ d ‐Glc p ‐(1→3)‐α‐ d ‐Glc p ‐(1→} or cyclic nigerosyl‐(1→6)‐nigerose (CNN), as a chiral source. CNN was enzymatically produced from starch relatively recently, and so far, only the production, purification, and degradation behaviors have been investigated intensively .…”
Section: Introductionmentioning
confidence: 99%